PENGARUH BIAYA PRODUKSI DAN PROMOSI TERHADAP LABA BERSIH - Nur Laili, Illa Alfatica; Nugroho, Hendrato Setiabudi (Program Studi Manajemen, 2022)
The cosmetics and household goods sub-sector are industries that are fast and full of changes. These changes can be in the form of trends, types of products and also consumer profiles. The increase in the growth of the cosmetics industry by 20% in 2017 has an impact on increasing sales. Thus, production costs reduction needs to be done, so that it has a good impact on net income. Promotion is also needed so that the product is known by the wider community. Promotional costs used are also important to increase company profits. This study employed a quantitative approach using secondary data. The sample used was 6 companies in the cosmetics and household goods sub-sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The research instrument used was documentation. The results obtained are (1) production costs have a significant effect on net income with a significance result of 0.000 < 0.05; (2) promotion costs have no significant effect on net income with a significance result of 0.498 > 0.05; and (3) simultaneously production costs and promotion costs have an effect on net income with a significance result of 0.000 <0.05.